Mechanism of HIF1-α-mediated regulation of Tribolium castaneum metabolism under high CO2 concentration elucidated. (December 2022) - Wu, Zi-Qi; Guan, Li-Wen; Pan, Bi-Ying; Xu, Hai-Tian; Luo, Yu-Jia; Zhou, Min; Zhang, Jia-Yong; Wang, Shi-Gui; Li, Can; Tang, Bin
Abstract: HIF1-α is an inducer that plays an important role in the regulation of hypoxia stress in insects in the way of regulating the corresponding enzyme activity which depends on the oxygen concentration through the hydroxylation of proline residues. In this study, we silenced HIF1-α expression in the model insect Tribolium castaneum under a hypoxic environment to explore its role in regulating metabolism in T. castaneum . We found that ATP and NAD  +  contents decreased significantly after HIF1-α interference at normoxic conditions, while activity of the soluble trehalase increased. The expression of TRE1-2, TRE1-3, TRE2, and TPS genes in the trehalose metabolism pathway were highly enhanced which are compared with normoxic conditions. Meanwhile, the expression of InR2 was significantly up-regulated, both of which play an important role in metabolism. We speculate that the enhancement of the insulin metabolic pathway may lead to enhanced glycolysis. We propose that the HIF1-α gene effectively regulates metabolism for T. castaneum to adapt to high CO2 concentrations in the environment. Our results provide a solid theoretical basis for controlling stored-grain pests incidence using high CO2 treatment. Graphical abstract: Image 1 Highlights: HIF1-α expression was silenced in Tribolium castaneum under a hypoxic environment. ATP and NAD  +  contents decreased significantly after HIF1-α interference. Activity of soluble trehalase increased after HIF1-α interference. Enhancement of the insulin metabolic pathway may lead to enhanced glycolysis. HIF1-α regulates T. castaneum metabolism to adapt to high-CO2 environments.